CEC’s Standards for Classifying the Evidence Base of Practices in Special Education - Cook, Bryan G.; Buysse, Virginia; Klingner, Janette; Landrum, Timothy J.; McWilliam, R. A.; Tankersley, Melody; Test, David W. (Remedial and special education, 2015)
As an initial step toward improving the outcomes of learners with disabilities, special educators have formulated guidelines for identifying evidence-based practices. We describe the Council of Exceptional Children’s new set of standards for identifying evidence-based practices in special education and how they (a) were systematically vetted by expert special education researchers through a Delphi study, (b) demonstrated adequate inter-rater reliability in a pilot study, (c) delineate specific criteria in many areas and provide flexibility to tailor other criteria, (d) provide an integrated set of standards for classifying the evidence base of practices based on findings from both group comparison and single-subject studies, and (e) can be applied by independent special education researchers. We conclude by noting limitations to the standards, briefly comparing these new standards with other evidence-based practice standards, and providing recommendations for future research and for refining the standards.